Kinerja Infrastruktur Pelayanan Jaringan Jalan Kabupaten di Wilayah Pengembangan Timur Kabupaten Bogor - Djakapermanan, Ruchyat Deni; Hidayat, Janthy Trilusianthy (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
The Eastern Development Region (WP Timur) of Bogor Regency, consisting of 7 districts, holds a strategic position and is experiencing rapid development. WP Timur is currently in the process of forming a new "Bogor Timur" Regency and is also the site of several national strategic projects. Infrastructure development, particularly road networks, must be able to anticipate the region's growth and changing needs. To improve the management of road infrastructure, an evaluation of the road network's performance is required.. The methodology involves (1) comparing the existing road variable values with the performance standards set by government regulations, (2) analyzing the connectivity index of the county road network, and (3) conducting an integrative assessment based on the analysis of various variables. The results of this research indicate that (1) Cariu District meets the standards for 8 road performance variables, including having good connectivity. Jonggol, Sukamakmur, and Tanjungsari Districts meet 5 variables with deficiencies in accessibility, mobility, road condition, and connectivity. Gunung Putri, Cileungsi, and Klapanunggal Districts meet only 3 variables with deficiencies in accessibility, mobility, and road condition. Gunung Putri and Cileungsi have low traffic loads, while Klapanunggal lacks connectivity. (2) New road construction is needed in Gunung Putri, Cileungsi, Klapanunggal, and Jonggol Districts based on Accessibility SPM, and in Gunung Putri, Cileungsi, Klapanunggal, Sukamakmur, and Tanjungsari Districts based on Mobility SPM. The construction of new roads aims to anticipate increased traffic volume and enhance connectivity. (3) Efforts are required to improve road conditions and maintenance in the 6 districts other than Cariu based on Road Condition SPM